2021
DOI: 10.1080/1091367x.2021.1874955
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Movement Skills and Their Assessment in Primary Schools from the Perspective of Teachers

Abstract: Evidence suggests that children struggle to acquire age-appropriate fundamental movement skills (FMS), despite their importance for facilitating physical activity. This has led to calls for routine school-based screening of children's FMS. However, there is limited research exploring schools' capacity to conduct such assessments. This study investigated what factors might affect the adoption and implementation of FMS assessments in primary schools. School staff (n = 853) completed an online questionnaire devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In fact, physical educators cited the lack of FMS knowledge, insufficient support and time requirements as major barriers to assessments of these skills at schools. 30 The developed FMS Rater has potential to overcome these barriers since the tool does not require teachers to have an in-depth knowledge in FMS. The time required to complete the access Open access assessments, and that to receive feedback and results, can also be reduced greatly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, physical educators cited the lack of FMS knowledge, insufficient support and time requirements as major barriers to assessments of these skills at schools. 30 The developed FMS Rater has potential to overcome these barriers since the tool does not require teachers to have an in-depth knowledge in FMS. The time required to complete the access Open access assessments, and that to receive feedback and results, can also be reduced greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Using simple biomechanical principles, this application allows teachers to provide real-time assessment to children’s performances in FMS. In fact, physical educators cited the lack of FMS knowledge, insufficient support and time requirements as major barriers to assessments of these skills at schools 30. The developed FMS Rater has potential to overcome these barriers since the tool does not require teachers to have an in-depth knowledge in FMS.…”
Section: Discussionmentioning
confidence: 99%
“…The survey consisted of between 19 and 23 items (including demographic questions), depending on whether the child; (1) currently (n = 21), (2) previously (but no longer) (n = 23), or (3) had never (n = 19) used a wearable. Questions were developed based on previous research using the same theoretical underpinnings (TDF, COM-B model) (Creaser et al 2022;Eddy et al 2021), and were derived based on the recommendations and terminology outlined by Michie et al (2015) (e.g. using examples from the 'COM-B self-evaluation questionnaire'; Michie et al 2015) The face validity of the survey items was evaluated by a multi-disciplinary team (n = 5), who provided critical insights into the appropriateness of the items, compared to the definitions outlined by Michie et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…FMS is the ability to perform three basic movement skills such as locomotor skills, sta-bility skills, and manipulative/object control skills (Engel, Broderick, Broderick, Hardy & Parmenter, 2018;Platvoet et al, 2018;Behan, Belton, Peers, O'Connor & O'Connor, 2019). FMS is an important factor that causes students to be able to perform physical movements in physical education classes (Eddy et al, 2021;Basman, 2019;Lawson, Eyre, Tallis & Duncan, 2021), and various kinds of physical activities (Haegele, Brian & Brian, 2015). There were some data reported that the FMS aspect of students during the pandemic has decreased significantly (Bai et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%